Phosphorene: Physical Properties, Synthesis, and Fabrication - Cai, Yongqing; Zhang, Gang; Zhang, Yong-Wei (Pan Stanford Publishing, 2018)
"This book is the first attempt to systematically present the knowledge and research progress of phosphorene, another elemental 2D material that can be exfoliated by mechanical or liquid methods as the intensively studied graphene. The book provides a comprehensive overview of the synthesis, growth, characterization, and applications of phosphorene. It also compiles cutting-edge research in the related field with respect to thermal conduction, transistors, and electrochemical applications and encompasses the intrinsic properties (structural, electronic, defective, and phononic) of phosphorene. Edited by Yongqing Cai, Zhang Gang, and Yong-Wei Zhang, three prominent theoretical researchers, this book provides detailed mechanisms of phenomena observed for phosphorene. It will benefit graduate students of physics, chemistry, electrical and electronics engineering, and materials science and engineering; researchers in nanoscience working on phosphorene and similar 2D materials; and engineers and anyone involved in nanotechnology, nanoelectronics, materials preparation, and device fabrication based on layered materials."--Provided by publisher.
OCLC-licensed vendor bibliographic record.
Keywords: Phosphorus; Electromagnetism; Microwaves; Materials science; Optoelectronics; SCIENCE / Physics; SCIENCE / Life Sciences / General; TECHNOLOGY / Material Science